Pengaruh Media Pembelajaran (Mopurat) Digital Terhadap Peningkatan Keterampilan Menulis Siswa Kelas VII MTS Al-Hidayah - Widiarti, Melia; Pairin, Udjang; Indarti, Titik (Jayapangus Press, 2024)
In the world of education, Indonesian is one of the subjects that must be taught to students. Indonesian covers the fields of language and literature. In literary activities, writing poetry requires teacher guidance. Learning to write poetry using the monopoly media of folk poetry (MoPuRat) is a concept that presents monopoly as a visual-based medium. This research aims to build the writing skills of many students who are still less active. This type of research is an experiment with a quantitative description method. This research is a type of true experimental design or actual research. The population in this study were all class VII students at MTs Al-Hidayah, while the sample used was class VII-D as the control class and VII-C as the experimental class. The data collection techniques used are observation, tests and questionnaires. Data analysis techniques use formulas to calculate student and teacher activities, test and posttest results, and student response questionnaire results. The results of the research show that the application of folk poetry monopoly media (MoPuRat) in learning to write folk poetry goes well and smoothly. In the control class the average test value was 71.12 and the average posttest value was 77.84. Meanwhile, in the experimental class the average pre-test score was 72.133 and the average post-test score was 87.133. Even though the average score of the two classes increased, the experimental class increased more than the control class. There is a significant difference in learning to write poetry between the control class and the experimental class. This is evident from the results obtained t0 = 2.9882 with db 53. Based on the calculation table, t0 is greater with ttotal at t0 0.005 = 2.00 and t0 0.001 = 2.9882.